(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Gross Domestic Product (GDP) is one of the most important macroeconomic indicators for the developed level and the economic growth and development dynamic of the each country. GDP in the Republic of Macedonia has increase tendency with average annual rate (AAR) from 7,4 % for the period 2006–2011. GDP per capita follow that trend with the AAR from 7,2 %. Parallel with the increase of the total GDP has grow and for the value added in the manufactur-ing with the AAR from 4,5 % and also in the furniture production with AAR from 1,7 % for the same period. The value added at manufacture of wood and wood products has negative trend with AAR from -7,7 %. The average annual value added of the manufactory of wood and wood products participates with 1, 5 % in the average annual value added of the total manufacturing, respectively with 0,2 % in the average annual GDP. The average annual value added at furniture production participates with 2,0 % in the average annual value added of the manufacturing and with 0,3 % in the average annual GDP for the analyzed period.